Analisis Empiris Pengaruh Gopay Digital Financial Literacy dan Mobile Payment Behavior Analytics terhadap Personal Financial Management Accounting dengan Moderasi Financial Self-Control - Ni Putu Ayu Cahya Sudertiani; Putu Putri Prawitasari (ManBiz: Journal of Management and Business, 2025)
The development of financial technology has driven the increasing use of digital wallets such as GoPay, especially among millennials and Generation Z. The ease of digital transactions, on the one hand, provides efficiency, but on the other hand, has the potential to trigger consumptive behavior that can weaken personal financial management. This study aims to analyze the influence of GoPay Digital Financial Literacy and Mobile Payment Behavioral Analytics on Personal Financial Management Accounting, with Financial Self-Control as a moderating variable. This study uses a quantitative approach with a survey method through a Likert-scale-based questionnaire. The research sample consisted of 160 respondents who were active GoPay users aged 18–35 years and domiciled in Denpasar City. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS software. The results of the study indicate that GoPay Digital Financial Literacy has a positive and significant effect on Personal Financial Management Accounting. Mobile Payment Behavioral Analytics has also been shown to have a positive and significant effect on Personal Financial Management Accounting. In addition, Financial Self-Control has been shown to moderate the influence of GoPay Digital Financial Literacy and Mobile Payment Behavioral Analytics on Personal Financial Management Accounting, thereby strengthening individuals' ability to manage personal finances in a more disciplined and structured manner. These findings indicate that digital financial literacy and good transaction behavior patterns need to be balanced with financial self-control so that the use of digital wallets can have a positive impact on personal financial well-being.